Numerical heat transfer study of square duct equipped with novel flapped V-baffles - Thianpong, Chinaruk; Promvonge, Pongjet; Skullong, Sompol; Promthaisong, Pitak; Nakhchi, Mahdi Erfanian (My University, 2024)
The paper describes a computational study of heat transfer enhancement inside a square duct with V-shaped flapped baffles located repeatedly on the bottom and top walls for fluid flowing with Reynolds numbers (Re) from 3000 to 21,000. The basic goal of this work is to attain the largest relative Nusselt number (Nu/Nu0) whilst maintaining the highest thermal performance to improve energy savings. A finite volume method was used in the computations, along with the Realizable k‒ε turbulent model. The variable baffle parameters considered first in the current simulation were the relative height/blockade ratio (BR = 0.05−0.2) and the flap angle of the baffle hole (β = 0° − 90°), while the fixed parameters included the attack angle (α = 60°), hole diameter ratio (dR = 0.5), and pitch ratio (PR = 0.5). To accomplish this goal, the previously mentioned parameters providing the best thermal performance were investigated further by extending the values of BR to 0.25−0.3, dR to 0.8 and α to 45°−30°. The simulation results indicate that the jet flowing from the flapped hole, as well as the vortices created by the baffle, can boost heat transfer and friction loss in comparison to the plain duct. In comparison, using a flapped baffle with β > 0° results in less friction loss, a greater thermal enhancement factor (TEF), and a higher Nusselt number than using a baffle with no flap. The first investigation disclosed that for BR = 0.2 and β = 20°, the greatest TEF of 2.19 with Nu/Nu0 of 7.9 times are obtained. The extended study, on the other hand, showed that the highest TEF of roughly 2.49 with Nu/Nu0 of 8.4 times are seen for α = 45°, dR = 0.8, BR = 0.25 and β = 20° at lowest Re. Thus, the flapped baffle provides a significant increase in Nu/Nu0 and TEF over the baffle alone.
Keywords: Flapped baffle; Friction factor; Heat transfer; Thermal performance; Turbulent flow